Involvement of WNT signaling pathway in the adult hippocampal synapses :role in neuroprotection. - Vargas Galarce, Jessica Yelena. (2014)
Tesis (Doctor en Ciencias Biológicas, mención en Biología Celular y Molecular)--Pontificia Universidad Católica de Chile, 2014.